On the instability of one nonautonomous essentially nonlinear equation of thenth order - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish sufficient conditions for the Lyapunov instability of the trivial solution of a nonautonomous equation of thenth order in the case where its limit characteristic equation has a multiple zero root. The instability is determined by nonlinear terms.